Oscillations in Difference Equations with Deviating Arguments and Variable Coefficients - G. E. Chatzarakis; H. Péics; I. P. Stavroulakis (Abstract and Applied Analysis)
New sufficient conditions for the oscillation of all solutions of difference equations with several deviating arguments and variable coefficients are presented. Examples illustrating the results are also given.